Using experience-based design to understand the patient and caregiver experience with delirium - Lauren Russ; Jennifer Phillips; Val Ferris; Amy London; Logan Kendall; Craig Blackmore (The Beryl Institute, 2019)
Hospital-acquired delirium negatively affects clinical outcomes and the care experience for patients and family caregivers. Following the qualitative methods of experience-based design, we completed observations of hospital units and interviews of patients, caregivers (including family members and other companions), and hospital nurses and other staff regarding their experiences with delirium. In addition, we administered an experience-based design questionnaire to another 130 subjects from the same groups. Key findings included: there is a need for preparation of the patients and family caregivers for the possibility of delirium (particularly before surgery), and patients and caregivers lack understanding of delirium and its potential prolonged aftereffects. We identified that caregivers may both contribute and detract from delirium care as they: (1) often identify delirium early; (2) are invaluable for supporting patients during re-orientation after delirium episodes; (3) frequently lack the preparation and skills for adequate delirium detection and response; (4) may not be present at critical times; (5) can be challenging for the delirium management team, and (6) are frequently discussed as the person who best understands the patients' baseline cognitive state and behavior. Experience-based design is an innovative framework to increase our qualitative understanding of the patient and caregiver experience during and following episodes of hospital acquired delirium.